KEPRIBADIAN TOKOH DALAM CERPEN ASY’AB FĪ BILĀDI WAQ WAQ 2002) DAN ASY’AB FĪ MINCHAH (2002) KARYA WAJĪH YA’QUB AS-SAYYID: KAJIAN PSIKOLOGI SASTRA SIGMUND FREUD - Nurul Khoidah, Afnan Arumi (Arabic Literature Department, 2016)
This article aims to explain the structural text of Asy'ab fī Bilādil Wāq Wāq (2002) and Asy'ab fī Michnah (2002) by Wajī h Ya'qub As-Sayyid by using Burhan Nurgiyantoro‟s structural theory. So, The purpose of this study focused to describes the structural text of both. The results shows that: first, The text structure in the short story Asy'ab fī Bilādil Wāq Wāq (2002) and Asy'ab fī Michnah (2002) is built with 6 (six) elements. Second, The characters in the short story of both text are categorized into two :Protagonist and antagonist. (1) the protagonist is represented by the figure: (a) Asy'ab with a number of personalities such: Wise, patient, trustworthy, responsible, broad-minded, hard work, humble and calm; (b) Great chef with his personality: Care for others and firm; (c) servants with his personality: Honest and submissive; (d) friends with personality: Likes to help and care for others; (e) Asy'ab's wife with her personality: Care for her husband, (2) the antagonist is represented by a character: (a) Governor with a number of personalities: hunatic, emotional and greedy; (b) Minister with a number of personalities: Evil, stubborn, nonchalant and greedy.